(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The most learning model known moment this and have Lots used in learning is the cooperative model . Learning cooperative is one of the models during This Already often used , with objective For increase participation participant educate, facilitate participant educate with experience attitude leadership and create decision in group, as well give opportunity for participants educate For interact and learn together with different friends background behind. With learning cooperative participant educate Work in a manner collaborative For reach something objective together, as well as participants educate will develop Skills relate with fellow man who will useful outside school . this in accordance with opinion Enggen and Kauchak. Learning cooperative is A learning strategy groups that involve participant educate work in a manner collaborate for reach objective together.